Model-driven domain analysis and software development : architectures and functions - Osis, Janis, 1929-; Asnina, Erika, 1978- (Information Science Reference, 2011)
"This book displays how to effectively map and respond to the real-world challenges and purposes which software must solve, covering domains such as mechatronic, embedded and high risk systems, where failure could cost human lives"--Provided by publisher